THE AGREEMENT ON TRADE-RELATED ASPECTS OF INTELLECTUAL PROPERTY RIGHTS (TRIPS) - Alina BABA (Annals of the University of Oradea: Economic Science)
The paper delves into the development and intricacies of international legal frameworks for intellectual property (IP) rights protection and commercialization, focusing on agreements like the Paris and Berne Conventions. It outlines the evolution from initial measures safeguarding industrial property to broader copyright and trademark protections, facilitated by entities such as the World Intellectual Property Organization (WIPO) and the World Trade Organization (WTO). The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) is highlighted for establishing minimum standards for IP protection and enforcement, integrating provisions for dispute resolution, and managing the balance between IP holders’ interests and the public good. TRIPS’ role in addressing challenges posed by differing national norms and its efforts to mitigate IP rights abuse through limitations and exceptions, known as the Three-Step Test, are emphasized. This analysis underscores the importance of a fair and balanced IP system that promotes global innovation and creativity, acknowledging the need for a harmonious integration of varied national laws within the global trade and IP protection landscape.